2020
DOI: 10.1136/ejhpharm-2020-002500
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a novel home delivery service during pandemic

Abstract: Introduction During the COVID-19 pandemic, measures have been put in place to adapt to patients' needs during home quarantine, such as "telehealthcare". With this service, hospital pharmacists develop a distinct role via the implementation of pharmacovigilance services and pharmaceutical care plans for patients with comorbidities, and for special populations as immunosuppressed patients. Methods Cross-sectional study involving hospital and community pharmacists actively practising during the COVID-19 pandemic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 10 publications
3
27
0
Order By: Relevance
“…Reimbursement issues were also noted by one case study from Bangladesh [ 47 ]. A challenge not noted by expert opinion was limited legislation allowing implementation of telepharmacy; this was also seen in the literature review articles [ 37 , 41 , 47 ]. The literature reviews also discovered that pharmacists lacked appropriate training related to disaster management and had difficulty navigating the COVID-19 pandemic [ 46 ].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Reimbursement issues were also noted by one case study from Bangladesh [ 47 ]. A challenge not noted by expert opinion was limited legislation allowing implementation of telepharmacy; this was also seen in the literature review articles [ 37 , 41 , 47 ]. The literature reviews also discovered that pharmacists lacked appropriate training related to disaster management and had difficulty navigating the COVID-19 pandemic [ 46 ].…”
Section: Resultsmentioning
confidence: 96%
“…The most commonly observed telepharmacy initiatives were virtual consultations, home delivery of medicines and patient education based on case studies and original research articles [ 35 , 37 , 38 , 39 , 41 , 42 , 43 , 45 , 46 , 47 , 48 ]. At least one case study from a cancer institute reported offering telepharmacy to patients at-risk [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a survey of 185 Spanish public hospitals, 83.2% of PS did not include medication delivery as part of their remote pharmaceutical care service prior to the health crisis 11. The declaration of the state of alarm on 14 March 2020 presented PS with an opportunity to develop and implement new models of remote care and remote medication dispensing 12–15…”
Section: Discussionmentioning
confidence: 99%